The performance of the islamic balanced fund in Malaysia / Farahah Mohd Said - Mohd Said, Farahah (Faculty of Business and Management, 2011)
This study is concerned about the Performance of Islamic Balanced Fund in Malaysia which covers the period of 2004 until 2010. In this study consists of ten companies of balanced fund which is Affin Dana Islamiah, Alliance Dana Alif, AMB Dana Ikhlas, CIMB Islamic Balanced, Avenue Syariah Extra, Hong Leong Dana Maa'rof, Apex Dana Al-Faiz-I, Prudential Dana Al- Islah, RHB Mudharabah, and ASBI Dana Al-Munsif. The objectives of this study are to determine the performance among ten companies by using three methods which is Sharpe, Treynor, and Jensen Perfomance. This done by measuring the performance of balanced fund, that is the quarterly return of ten balanced fund and also quarterly return of FTSE Bursa Malaysia Emas Shariah Index. According to the result performance of balanced fund, the risk and return each of fund can be identified from this measurement. In time series of regression will be used to determine whether each of balanced funds has a significant and positively related with FTSE Bursa Malaysia Emas Shariah Index.